Frequency of Pyrethroid Insecticide Resistance kdr Gene and Its Associated Enzyme Modulation in Housefly, Musca domestica L. Populations From Jhang, Pakistan - Riaz, Bushra; Kashif Zahoor, Muhammad; Malik, Kausar; Ahmad, Aftab; Majeed, Humara Naz; Jabeen, Farhat; Zulhussnain, Muhammad; Ranian, Kanwal (Frontiers in Environmental Science, 2022)
House fly, Musca domestica is considered responsible of transmitting wide variety of human and veterinary diseases. Mostly, insecticides are being used for their control and more commonly, pyrethroid insecticides worldwide. However, resistance has been reported against various pyrethroid insecticides. House flies become resistant by two major mechanisms, i.e., target site insensitivity through knockdown resistance gene mutation (kdr) and enzyme detoxification. Thus, the current study was designed to monitor the frequency of pyrethroid resistance gene kdr in house fly populations of District Jhang. The flies were collected from seven sampling sites and then reared in the lab for molecular and biochemical assays. The amplification of template DNA was performed for knock down resistance gene through the outer primers kdr1 and kdr4, and the inner primers kdr1 and kdr2 using PASA (PCR Amplification of Specific Alleles) method which specifically amplify the domain-II of kdr gene. Three populations were found homozygous susceptible (+/+; 42.85%); whereas two populations were found genetically homozygous resistant (-/-; 28.57%) which are insensitive to pyrethroid insecticides. Similarly, two populations were found heterozygous (+/-; 28.57%) for kdr suggesting thereby that at least 1/4th homozygous resistant (-/-) house fly populations with insensitivity to pyrethroids would be produced in future keeping in view the Mendelian ratio. Biochemical assay showed that homozygous resistant populations had increased activity of Acetylcholinesterase (AChE), α-Carboxylesterases (α-Carboxyl), β-Carboxylesterase (β-Carboxyl), Alkaline Phosphatase (AkP) and Acidic Phosphatase (AcP) enzymes. In addition, heterozygous populations also showed increased activities of these enzymes. The current results would not only help avoid the indiscriminate load of insecticides onto environment but also serve as hallmark for the management of house fly populations in target areas in future.